Differentially expressed proteins in the intestine of Cynoglossus semilaevis Günther following a Shewanella algae challenge. Issue 104 (September 2020) - Han, Zhuoran; Sun, Jingfeng; Wang, Anli; Lv, Aijun; Hu, Xiucai; Chen, Limei; Guo, Yongjun
Abstract: Fish intestine is an important constituent of the mucosal immune system. The gut and gut-associated lymphoid tissue construct a local immune environment. A Shewanella algae strain was previously reported to be a pathogen causing ascitic disease accompanied with intestinal inflammation in Cynoglossus semilaevis . This study aimed to investigate the intestine immune response in C. semilaevis to S. alga e infection at the protein level. Two-dimensional electrophoresis coupled with mass spectrometry proteomics was utilized to compare protein expression in the intestines from normal and S. algae -infected C. semilaevis . A total of 70 differentially expressed proteins (DEPs), consisting of 16 upregulated and 54 downregulated proteins, were identified in the intestine tissue of C. Semilaevis . These protein expression changes were further validated using western blot analysis and quantitative real-time PCR. Gene ontology enrichment analysis showed that these 70 DEPs could be assigned across three categories: "cellular components", "molecular function", and "biological process". Forty-one DEPs (six up-regulated and 35 down-regulated proteins) related to metabolic processes were identified. In addition, 20 DEPs (eight up-regulated and 12 down-regulated proteins) related to stress and immune responses were identified. A protein-protein interaction network generated by the STRING (Search Tool for the Retrieval of Interacting Genes/protein) revealed that 30 DEPs interacted with one another to form an integrated network. Among them, 29 DEPs were related to stress, immune, and metabolism processes. In the network, some of the immune related proteins (C9, FGB, KNG1, apolipoprotein A-IV-like, and PDIA3) were up-regulated and most DEPs involved in metabolism processes were down-regulated. These results indicate that the immune defense response of the intestine was activated and the intestinal function associated with metabolism processes was disturbed. This study provides valuable information for further research into the functions of these DEPs in fish. Highlights: The protein expression was compared in intestine of normal and S. algae -infected C. semilaevis. Seventy differentially expressed proteins (DEPs) were identified. Protein-protein interaction analysis indicated that 29 DEPs were interrelated. The immune defense was activated and metabolic processes were disturbed in intestine.